Survei aktivitas fisik mahasiswa prodi Pjkr Universitas Pgri Semarang angkatan 2017 pada masa pandemi covid-19 - Reza Naufal Azzami Teguh Wibowo; Buyung Kusumawardhana; Galih Dwipradipta (Journal of Physical Activity and Sports (JPAS), 2021)
This research was motivated by the conditions of the covid-19 pandemic in Indonesia and changing the education system from face to face to online. This is coupled with the number of campus activities and online assignments, especially for students of the 2017 PJKR study program at PGRI Semarang University. The purpose of this study was to determine the physical activity of students of the PJKR study program at PGRI Semarang University during the pandemic. This research uses survey research with descriptive analysis method with percentage technique. The sampling technique used is the Simple Random Sampling technique. The results of this study, according to the description of the data and the discussion studied by the researcher, are that the 2017 PJKR PGRI Semarang University students are aware and consider it important to carry out physical sports activities during this pandemic. This is evidenced because on average they do various types of sports, jogging is the most popular choice. Suggestions that can be given are in the form of collaboration between lecturers and students to work together in socializing related to breaking the chain of the spread of Covid-19 through the role of student education in their families and the environment around their respective homes or villages.